Low Cost Portable Wind Power Generation For Mobile Charging Applications - Rajan, R.; Panchalogaranjan, V.; Aravinthan, V.; Thiruvaran, T.; Vinothine, S. (IEEE, 2018)
Wind energy based power generation has become one of the focal points in the research of renewable energy sources. Mobile phones are essential communication devices nowadays but still people face difficulties in mobile phone charging where the utility supply is not available. This paper presents a design and implementation of a small scale low speed wind power based portable mobile phone charger. The implementation includes a savonius wind turbine and a controller. According to the speed change of the wind, the output voltage of the generator changes from 1V to 3V so a controller is designed to control a DC-DC boost converter to get a constant output voltage. The formal approach of the PI control scheme is used in the design of the controller. The integrated device is able to produce the desired output voltage to charge the mobile phone. This device provides green energy for mobile phone charging where the utility is not available.
Keywords: Portable; Savonius wind turbine